American Oral History Archives on Slavic Immigration. An Overview of Preserving Slavic Immigrants’ Life Stories - Bantiou, Marina (Migrations in the Slavic Cultural Space. From the Middle Ages to the Present Day, 2022)
This paper presents selected archival oral history collections and projects conducted in the United States based on the testimonies of Slavic immigrants to the US during the 20th century. It focuses on an overview of important existing archives of oral testimonies in the US. The aim is to create a “mapping” of oral history archives on the above subject and present aspects of Slavic immigration to the US in parallel. The experiences and life stories of first and second generation immigrants in the US are presented in categories per collection, emphasizing their valuable importance for contemporary history and highlighting the importance of “history from below”, which is based on the value of personal experience.